2017
DOI: 10.3390/economies5010004
|View full text |Cite
|
Sign up to set email alerts
|

Financial Deepening and Economic Growth Nexus in Nigeria: Supply-Leading or Demand-Following?

Abstract: This paper examined the direction of causality between financial deepening and economic growth in Nigeria for the period 1970-2013. The study adopted the Toda-Yamamoto augmented Granger causality test and results showed that the growth-financial deepening nexus in Nigeria follows the supply-leading hypothesis. This means that it is financial deepening that leads to growth and not growth leading financial deepening. Among other things, the study recommended that policy efforts should be geared towards removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 19 publications
5
28
0
1
Order By: Relevance
“…Another reason adduced for this inverse relationship may be the weak monetary policy by the apex bank over time and weak framework. The finding agrees with the research outcome by Ajao and Festus (2011); Igbinosa and Orobator (2016); Partar (2016); Etale and Ayunku (2017) and Karimo and Ogbonna (2017). It however disagrees with the researches of Iyiegbumiwe (2005); Agbada and Odejimi (2013); Ndugbu et al (2015); and Okoro et al (2017).…”
Section: Empirical Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…Another reason adduced for this inverse relationship may be the weak monetary policy by the apex bank over time and weak framework. The finding agrees with the research outcome by Ajao and Festus (2011); Igbinosa and Orobator (2016); Partar (2016); Etale and Ayunku (2017) and Karimo and Ogbonna (2017). It however disagrees with the researches of Iyiegbumiwe (2005); Agbada and Odejimi (2013); Ndugbu et al (2015); and Okoro et al (2017).…”
Section: Empirical Analysissupporting
confidence: 81%
“…This study adapts the empirical models of Igbinosa and Orobator (2016), Karimo and Ogbonna (2017), Etale and Ayunku (2017). The functional form of the model is: This study adapts the empirical models of Igbinosa and Orobator (2016), Karimo and Ogbonna (2017), Etale and Ayunku (2017). The functional form of the model is: = , , ,…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatti (2015) indicated positive relationship between financial depth and economic growth in Pakistan. Karimo and Ogbonna (2017) confirmed that the growth-financial deepening nexus in Nigeria follows the supply-leading hypothesis. However, Adusei (2013) explored evidence that financial development undermines economic growth in Ghana.…”
Section: Literature Reviewsupporting
confidence: 52%
“…The Granger causality test showed the presence of unidirectional relationship among variables. [27] examined the direction of causality between financial deepening and economic growth in Nigeria for the period 1970-2013. The study adopted the Toda-Yamamoto augmented Granger causality test and results showed that the growth-financial deepening nexus in Nigeria follows the supply-leading hypothesis.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%